Are We Missing out on Half of All Heat-treated Pieces in the Solutrean?. (2nd January 2020) - Schmidt, Patrick; Morala, André
ABSTRACT: The European Solutrean has yielded one of the oldest chert assemblages documenting intentional heat treatment. Many questions about social and economic factors arise in this context. For example, did Solutrean knappers heat-treat only specific types of chert? Were specific heating techniques adapted to specific types of chert? We investigate these questions by analyzing 43 chert artifacts from Laugerie-Haute. We use near-infrared spectroscopy to identify heat-treated artifacts made from four different types of chart, and to estimate their heating temperatures. We identify 13/37 test pieces as heat-treated. Only 5 of these 13 pieces (38%) would have been identified as such macroscopically (based on gloss contrast). The overall magnitude of gloss, cannot be used to identify heat-treated chert artifacts. These findings have implications for future studies of the prevalence of heat-treated artifacts in Solutrean assemblages. Visual identification based on surface gloss is likely to only recognize the smaller part of heat-treated artifacts.